Avrupa para birliği, uygulamaları ve Türkiye etkileri - Tezuçan, Yasemin (My University, 2006)
Örgütlü kimliğini 20. yüzyılda ortaya koyan, bugün 25 üyeli Avrupa Birliği’nin nihai hedefi siyasi birliktir. Yaşanılan deneyimler de siyasi birliğin sağlanabilmesi için, Ekonomik ve Parasal entegrasyonun gerekliliğini ortaya koymuştur. Üye ülkeler arasında Ekonomik ve Parasal Birlik sağlanmış ve bu alanda entegrasyonun son aşaması olan tek paraya geçiş, ulusal paraların dolaşımdan çekilerek yerini “Euro” ya bırakması ile tamamlanmıştır. Euro tedavüle girdiği andan itibaren kuvvetlenerek, dünyanın en güçlü ikinci parası haline gelmiştir. Türkiye, daha “Euro Bölgesi” oluşturulmadan, 1959 yılında, Avrupa’da meydana gelen bu örgütlü yapıya katılma isteğini belirtmiş, 3 Ekim 2005 tarihinde Katılım Müzakerelerinin başlatılması ile bu istek somutlaşmaya başlamıştır. Ancak Türkiye’nin tam üyeliğe kabulünün uzun yıllar sürmesi beklenmektedir. Tam üyeliğe giden bu süreçte Türkiye’nin, Ekonomik ve Parasal Birliğe uyum için gerekli ekonomik ve yapısal reformları gerçekleştirip, “Euro Bölgesi” içersinde yer alması beklenmektedir. Bu çalışmada, Türkiye ile Avrupa Birliği arasındaki ilişkiler, önemli Antlaşmalar, Türkiye’nin uyum sürecinde gerçekleştirdiği reformlar irdelenmiştir.

The final objective of the European Union, the institutional structure of which was laid in the twentieth century, and which consists of 25 members at present, is a political union. Experience has shown that economic and monetary union is essential in order to achieve this target. So far, economic and monetary unity has been reached between the memeber states for the integration which was to replace the member countries’ currencies with a single European currency, namely “Euro” has been put into effect by drawing the national currencies from circulation. From the very first moment “Euro” war introduced, it started to gain value and soon became the world’s second strongest currency. In 1959, before the “Euro Zone” was formed, Turkey applied to become a member of the European Economic Union which is the initial body of the Eurpean Union. The wish to be a part of this union reached a more promising phase when the EU membership negotiations started on September 3, 2005. Nevertheless, Turkey’s acceptance into the union is expected to take a long time. During the process leading to full membership, Turkey is required to make the economic and structural reforms necessary for the convergance with the Economic and Monetary Union to be able to take part in the “Euro Zone” The main purpose of this study is to analyze the relationship of Turkey with EU and crucial agreements and reforms Turkey has to make for joining the European Economic and Monetary Union.
Keywords: Avrupa Para Birliği; Mali Hukuk; Para Politikası_Avrupa Birliği; Para_Avrupa Birliği